Real-life Use of Bexarotene for T-cell Cutaneous Lymphoma Management: Efficacy and Tolerance with Low Doses - Jacques Rouanet; Ines Joulie; Celine Lambert; Michel D'Incan (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)